Into the 21st century: management accounting trends - Robert Williams (Jurnal Akuntansi dan Auditing Indonesia, 1997)
This papaer consider the role of management accounting in organizations. It goes on to discuss some of the issue that currently impact on management accounting in the last three years of the twentieth century and will continue to do so into the next century.